Bibliometrics of Physical Therapy in Brazil: na analysis based on the profession specialties (Fisioterapia e Pesquisa, 2016)
Physical therapy lacks bibliometric analyses that report the most relevant aspects of its scientific production, as well as the profile of publications of the several specialties of this profession. This bibliometric analysis aimed to evaluate the articles published in Brazilian journals in the field of Physical Therapy and verify their relationship with the profession specialties. This cross-sectional study involved 15 journals with a focus on Physical Therapy, considering articles published between 2011 and 2014. Data of the journals were collected in each home page. We analyzed articles classified among the specialties of Physical Therapy, recognized by the Federal Council of Physical and Occupational Therapy. The Southeast region presented the greatest number of journals and the largest scientific production. Qualis B1 and B4 were the most frequent ones. Among the 2,683 articles, 1,664 (62%) were linked to the area of Physical Therapy. The time between submission and acceptance was 157 (68-243) days, and, from acceptance to publication, 109 (60-177) days. Trauma-Orthopedic Physical Therapy concentrated the highest number of publications (34.3%). Quantitative (80.8%) and human subject research (83.9%), as well as inferential statistics (67.7%), were the most frequent ones and prevailed among the specialties. Physical Therapy remains on the rise regarding the quantity and quality of its research in Brazil, glimpsing the growth of evidence-based professional practice in its various specialties. However, its articles still take a long time to be published. The higher prevalence of quantitative research and inferential statistics may promote substantial progress to the profession.